(untitled) (Medical Forum Monthly, 2026)
Objective: To determine the extent of thyroid, reproductive, and renal functions in hypothyroid women afterconsuming supplements of flaxseeds. Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Endocrinology and Oncology Center in Thi-qarfrom 1st April 2024 to 31st January 2025. Methods: 41 women aged 30-55 were enrolled. They were divided in 4 groups: healthy women without supplements group, hypothyroid women without supplements group, hypothyroid women where flaxseed was added to medication group and healthy woman who consumed only flaxseed group. The duration was 5 weeks, 1 week acclimatization period to the new diet and 4 weeks of daily flaxseed consumption, with a stepwise increase of the flaxseed dosage to a fixed endpoint. Results: The hypothyroid patients showed a prevalence of thyroid stimulating hormone, blood urea nitrogen, creatinine, and dysfunction of some reproductive hormones. Some renal parameters were evidenced to have decreased to normal values, follicle-stimulating horome, luteinizing hormone, estrogen, and testosterone were all restored, TSH was normal and flaxseed caused an elevation of T3. The healthy women’s parameters were all normal. It is plausible that a positive effect was brought about by the omega-3 fatty acid which assists the conversion of T4 to T3, the antioxidant boosting effect of the lignans and the support of the gut microbiome. Conclusion: Flaxseed could help reclaim these issues and restore hormones to a more healthy balance. Nevertheless, additional participants, larger samples, and extended studies are necessary to determine the efficacy of the treatment and assess the optimum dosage that can be administered alongside conventional thyroid medication.